2022
DOI: 10.1177/00185787211073464
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Potential Pharmacological Interactions in Patients Undergoing Systemic Chemotherapy in a Tertiary Hospital

Abstract: Introduction: Pharmacological interactions are frequently observed in patients with chronic diseases, and their occurrence is proportional to the amount of medication used daily. Patients undergoing chemotherapy treatment commonly have comorbidities, which favor a greater prevalence of polypharmacy, increasing the risk of drug interactions. Therefore, the aim of this study was to estimate the prevalence of drug interactions in patients undergoing intravenous chemotherapy treated at a hospital oncology service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
(114 reference statements)
0
3
0
1
Order By: Relevance
“…51 In addition, 67% severe and 26.9% moderate drug–drug interactions were observed among cancer patients undergoing chemotherapy. 52 The findings of the current study suggested a higher incidence of potential drug–drug interactions among gastrointestinal cancer patients. Therefore, it is essential to use drug interaction checker software in the study setting at the level of prescription and dispensing to minimise the significant morbidity associated with this undesired drug–drug interaction in gastrointestinal cancer patients.…”
Section: Discussionmentioning
confidence: 54%
“…51 In addition, 67% severe and 26.9% moderate drug–drug interactions were observed among cancer patients undergoing chemotherapy. 52 The findings of the current study suggested a higher incidence of potential drug–drug interactions among gastrointestinal cancer patients. Therefore, it is essential to use drug interaction checker software in the study setting at the level of prescription and dispensing to minimise the significant morbidity associated with this undesired drug–drug interaction in gastrointestinal cancer patients.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, active pharmacovigilance is crucial to ensure medication safety and to decrease the phenomenon of under-reporting. In addition, the pharmacist can monitor potential interactions, and this should be a valuable support for the oncologist [ 15 , 17 , 18 , 19 ]. Moreover, to reach correct the blood concentrations of oncological drugs, the oncologist should make use of Therapeutic Drug Monitoring (TDM).…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, possible DDIs have a high prevalence in oncology departments, where 80.8% of cancer patients treated at oncology service in a hospital located in southern Brazil were exposed to at least one interaction. 10 Although cyclophosphamide and doxorubicin are favored drugs in the treatment of breast cancer patients, 11 they are associated with a high risk of developing DDI. 12 In a study by Laban et al, Drugs.com identified potential DDIs (pDDIs) in 129 (84.9%) patients, while Lexicomp identified pDDIs in 113 (74.3%) patients in Northern Cyprus.…”
Section: Introductionmentioning
confidence: 99%